(untitled) (Dordrecht, 2000)
Breeding plants to encourage specific traits is usual in agriculture but less common in ornamental horticulture. Daffodils, daylilies, hostas, lilacs, magnolias, and rhododendrons are among the 15 subjects covered by experts in the field.
Keywords: Plants, Ornamental,Cây, cảnh; Breeding,Chăm sóc